Schoolhouse Gothic - A new direction for Gothic Studies - LIMA, Maria Antónia (2012)
Schoolhouse Gothic - A new direction for Gothic Studies Maria Antónia Lima Universidade de Évora / CEAUL (ULICES) Schoolhouse Gothic is a current trend in Gothic Studies that transfers the typical gothic fears of the past, lived in haunted mansions and created by inherited feudal powers, to school buildings and college campuses that function as their present analogues. It refers to a kind of fiction where characters are totally obsessed by the power of knowledge and by their superior hierarchical positions or social status, which may transform them into dehumanized beings, machines or monstrous creations. In Schoolhouse Gothic fiction, schools and universities enforce conformity and view independent thinkers as deviants that must be watched, punished, transformed, or eliminated. Schoolhouse Gothic literature includes works like Stephen King’s Carrie, Rage, Apt Pupil, and “Suffer the Little Children”; Flannery O’Connor’s The Violent Bear It Away; Toni Morrison’s Beloved; Joyce Carol Oates’s Beasts, and David Mamet’s Oleanna. In all these fictional examples, school buildings and classrooms are places of entrapment where individuals are victims of several forms of archaic authority established by some enlightened scholars and educators who seem to be totally blinded by their own prejudices rendering them complicit with unjust power structures. As Sherry Truffin concludes in Schoolhouse Gothic – Haunted and Predatory Pedagogues in Late Twentieth-Century American Literature and Scholarship, “The Schoolhouse Gothic suggests at the very least that Americans have become increasingly uneasy about the role of the academy, increasingly mistrustful of its guardians, and increasingly convinced that something sinister lies behind its officially benevolent exterior.” The ideal image of the academy as a haven for enlightened humanity can certainly be questioned by a disturbing reality that shows it as a place of mystified power and privilege where violence and mental disintegration may emerge like in a very typical gothic locus.